Post-exposure Lopinavir-Ritonavir Prophylaxis versus Surveillance for Individuals Exposed to SARS-CoV-2: The COPEP Pragmatic Open-Label, Cluster Randomized Trial. (December 2021) - Labhardt, Niklaus D; Smit, Mikaela; Petignat, Ianis; Perneger, Thomas; Marinosci, Annalisa; Ustero, Pilar; Diniz Ribeiro, Maria Pia; Ragozzino, Silvio; Nicoletti, Giovanni Jacopo; Faré, Pietro Benedetto; Andrey, Diego O; Jacquerioz, Frederique; et al.
Abstract: Background: Since the beginning of the COVID-19 pandemic, no direct antiviral treatment is effective as post-exposure prophylaxis (PEP). Lopinavir/ritonavir (LPV/r) was repurposed as a potential PEP agent against COVID-19. Methods: We conducted a pragmatic open-label, parallel, cluster-randomised superiority trial in four sites in Switzerland and Brazil between March 2020 to March 2021. Clusters were randomised to receive LPV/r PEP (400/100 mg) twice daily for 5 days or no PEP (surveillance). Exposure to SARS-CoV-2 was defined as a close contact of >15 minutes in <2 metres distance or having shared a closed space for ≥2 hours with a person with confirmed SARS-CoV-2 infection. The primary outcome is the occurrence of COVID-19 defined by a SARS-CoV-2 infection (positive oropharyngeal SARS-CoV-2 PCR and/or a seroconversion) and ≥1 compatible symptom within 21 days post-enrolment. ClinicalTrials.gov (Identifier: NCT04364022); Swiss National Clinical Trial Portal: SNCTP 000003732. Findings: Of 318 participants, 157 (49.4%) were women; median age was 39 (interquartile range, 28-50) years. A total of 209 (179 clusters) participants were randomised to LPV/r PEP and 109 (95 clusters) to surveillance. Baseline characteristics were similar, with the exception of baseline SARS-CoV-2 PCR positivity, which was 3-fold more frequent in the LPV/r arm (34/209 [16.3%] vs 6/109 [5.5%], respectively). During 21-day follow-up, 48/318 (15.1%) participants developed COVID-19: 35/209 (16.7%) in the LPV/r group and 13/109 (11.9%) in the surveillance group (unadjusted hazard ratio 1.44; 95% CI, 0.76-2.73). In the primary endpoint analysis, which was adjuted for baseline imbalance, the hazard ratio for developing COVID-19 in the LPV/r group vs surveillance was 0.60 (95% CI, 0.29-1.26; p =0.18). Interpretation: The role of LPV/r as PEP for COVID-19 remains unanswered. Although LPV/r over 5 days did not significantly reduce the incidence of COVID-19 in exposed individuals, we observed a change in the directionality of the effect in favour of LPV/r after adjusting for baseline imbalance. LPV/r for this indication merits further testing against SARS-CoV-2 in clinical trials. Funding: Swiss National Science Foundation (project no.: 33IC30_166819) and the Private Foundation of Geneva University Hospitals (Edmond Rothschild (Suisse) SA, Union Bancaire Privée and the Fondation pour la recherche et le traitement médical).